2021
DOI: 10.1111/1467-8500.12467
|View full text |Cite
|
Sign up to set email alerts
|

Does the talk match the walk for Australian local government employees: The link between leadership and employee well‐being

Abstract: There is a need to understand how leadership affects the well-being of local government employees working under conditions of prolonged austerity-driven reforms. A total of 118 Australian local government employees were surveyed. The analysis involved hierarchical regression using the PROCESS macro in SPSS, which identified the total, direct, and bootstrapped biascorrected indirect effects. The findings suggest that managers demonstrated some leadership behaviours required to lead staff positively; however, au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 68 publications
3
13
0
Order By: Relevance
“…However, no significant differences between the groups were observed in hope, resilience, or overall psychological capital scores. These studies align with prior research on psychological capital in public [57,[106][107][108][109] and private [110][111][112][113][114][115][116][117][118][119] sectors. However, it is unclear why the employees in public and private sectors differed in self-efficacy and optimism, but they did not differ in hope, resilience, or overall psychological capital.…”
Section: Public Sector Employees Partially Differ In Their Psychologi...supporting
confidence: 84%
See 2 more Smart Citations
“…However, no significant differences between the groups were observed in hope, resilience, or overall psychological capital scores. These studies align with prior research on psychological capital in public [57,[106][107][108][109] and private [110][111][112][113][114][115][116][117][118][119] sectors. However, it is unclear why the employees in public and private sectors differed in self-efficacy and optimism, but they did not differ in hope, resilience, or overall psychological capital.…”
Section: Public Sector Employees Partially Differ In Their Psychologi...supporting
confidence: 84%
“…Numerous studies have confirmed that psychological capital and its interventions are related to reduced work-related problems, not to mention positive wellbeing and workrelated outcomes [96][97][98][99][100][101][102][103][104][105]. Research of the psychological capital in the public sector has evidenced its' numerous benefits [57,[106][107][108][109]. Similarly, the studies on psychological capital in the business, entrepreneurial, or marketing contexts demonstrated the added value of psychological capital and its interventions for the private sector organizations [110][111][112][113][114][115][116][117][118][119].…”
Section: Psychological Capitalmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that it is the responsibility of those leading hospitals to ensure that their SLBs have adequate organisational resources to cope. Past research shows that leaders' behaviour (in terms of resourcing decisions and organisational support processes) can either erode or increase employee's perception of personal support (Adendorff et al, 2021). Walumbwa et al (2008, p. 84) defines authentic leadership as 'a pattern of leader behavior that draws upon and promotes both positive psychological capacities and a positive ethical climate, to foster greater self-awareness, an internalised moral perspective, balanced processing of information and relational transparency between leaders and followers'.…”
Section: Introductionmentioning
confidence: 99%
“…This means that it is the responsibility of those leading hospitals to ensure that their SLBs have adequate organisational resources to cope. Past research shows that leaders’ behaviour (in terms of resourcing decisions and organisational support processes) can either erode or increase employee's perception of personal support (Adendorff et al., 2021). Walumbwa et al.…”
Section: Introductionmentioning
confidence: 99%